STRATEGI PENYAMPAIAN HONORIFIK DALAM TINDAK PERINTAH MASYARAKAT TUTUR MAKASSAR - Syafruddin . (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
Honorific informative strategies play integral parts in Indonesian speech acts of the informed family of Makassar’s society. Those honorific informative strategies  have their unique  characteristics.  This study was conducted  to get the description and the explanation of honorific informative strategies in the Makassar’s informed family’s imperative speech acts. The design of this study was qualitative research by applying pragmatics theory design along with the ethnographic communication analysis model. The result of this study shows that honorific informative  strategies  were  implemented  through  imperative  and  interrogative speech  acts  which  used  a  variation  of  honorific  alternatives  based  on  different contexts suitable with their social and culture norms